The asean comprehensive investment agreement : The regionalisation of laws and policy on foreign investment - Chaisse, Julien
The International Investment regime is one of the fastest growing areas of international economic law which increasingly rely on large membership investment treaties such as the ASEAN comprehensive Investment Agreement. This book comprehensively examines the role of this specific agreement and situates it in the wider trend towards the regionalisation of laws and policy on foreign investment.